“Efecto de cuatro dosis de citrato de potasio en el cultivo de pepinillo (cucumis sativus L.) torneo 143 HyB MoS F-1 en el distrito de Lamas” - García Gonzáles, Katerine Coreya (2016)
The present work of investigation had as purpose to evaluate and determine the effect of the application of four doses of potassium citrate in the cultivation of cucumber (Cucumis sativus) hybrid Torneo 143 Hyb MoS F-1 with the trellis system for getting increases in performance and economic profitability in the conditions of Lamas district. "The Pacific" farm, property of Mr. Jorge Luis Pelaez Rivera, was the place of performance of the investigation, located politically in the district and province of Lamas, San Martin department. We used the Randomized Complete Block Design (RCBD) with five treatments and three replications, with a total of 15 experimental units. The information obtained in the field was processed with the statistical program called SPSS 19, which uses the p-value as a gauge of significant differences with the confidence levels of 0.05 and 0.01 in the analysis of variance (ANVA) and Duncan's multiple range test a p =